Association between anxiolytic/hypnotic drugs and suicidal thoughts or behaviors in a population-based cohort of students. (September 2020) - Lecat, Nicolas; Fourrier-Réglat, Annie; Montagni, Ilaria; Tzourio, Christophe; Pariente, Antoine; Verdoux, Hélène; Tournier, Marie
Highlights: 22.3% of students reported suicidal thoughts over the preceding year. 6.2% of students reported a lifetime suicide attempt. Anxiolytics/hypnotics were associated with STB, considering psychiatric symptoms. Anxiolytics/hypnotics did not attenuate the risk of subsequent STB. Abstract: Aims: To investigate the association between the use of anxiolytic/hypnotic drugs and suicidal thoughts and/or behavior (STB) in students. Methods: 12, 112 participants who completed the baseline questionnaire in the i-Share cohort between April 2013 and March 2017 were included. STB were defined at inclusion as suicidal thoughts over the previous year and/or a lifetime suicide attempt. The use of prescribed anxiolytic/hypnotic drugs over the previous 3 months was measured at baseline and follow-up time points (in 2, 919 students). Psychiatric disorders were assessed through validated scales. Multivariate logistic regression models were run using disease risk score. Results: At inclusion, 25.2% of students had STB and 10.3% used anxiolytics/hypnotics. STB at baseline were associated with a more frequent use of anxiolytics/hypnotics in the previous 3 months, after adjustment for covariates including anxiety, depression, sleep, impulsivity, and substance use. The use of anxiolytics/hypnotics at baseline was not associated with the occurrence, persistence or remission of STB one year later. STB at baseline were associated with a new anxiolytic/hypnotic treatment one year later. Conclusions: Anxiolytic/hypnotic drug use was associated with STB in students independently of many risk factors of suicide and most psychiatric disorders that require such treatment, which raises drug safety concerns.